Integration of VEK‐30 peptide enhances fibrinolytic properties of staphylokinase. (20th May 2020) - Bhando, Timsy; Singh, Satish; Hade, Mangesh Dattu; Kaur, Jagdeep; Dikshit, Kanak L
Abstract: Staphylokinase (SAK), a 136 amino acid bacterial protein with profibrinolytic properties, has emerged as an important thrombolytic agent because of its fibrin specificity and reduced inhibition by α‐2 antiplasmin. In an attempt to enhance the clot dissolution ability of SAK, a 30 amino acid peptide (VEK‐30) derived from a plasminogen (Pg) binding protein (PAM), was fused at the C‐terminal end of SAK with a RGD (Arg–Gly–Asp) linker. The chimeric protein, SAKVEK, was expressed in E. coli and purified as a soluble protein. Pg activation by equimolar complexes of SAKVEK and SAK with plasmin revealed that the fusion of VEK‐30 peptide has significantly enhanced the catalytic activity of SAK. The kinetic constant, k cat / Km, of SAKVEK for the substrate Pg appeared 2.7 times higher than that of SAK and the time required for the fibrin and platelet rich clot lysis was shortened by 30% and 50%, respectively. The binary activator complex of SAKVEK with plasmin gets inhibited by α2‐ antiplasmin but remains protected in the presence of fibrin, very similar to SAK. Thus, the present study suggests that SAKVEK is more potent and effective as a thrombolytic agent due to its higher catalytic activity for Pg activation in a fibrin‐specific manner and its ability to clear platelet‐rich plasma clot faster than SAK. Abstract : In this study, a novel chimera of a bacterial plasminogen activator, staphylokinase, was created that carries a RGD domain and a plasminogen‐binding peptide, VEK‐30. The chimeric protein, SAKVEK, displays enhanced thrombolytic properties due to its higher catalytic activity for the plasminogen activation on a fibrin and platelet‐rich blood clots.